Morphotaxonomic revision of Simulium (Gomphostilbia) (Diptera: Simuliidae) in the Oriental Region - Takaoka, Hiroyuki (Zootaxa, 2012)
Simulium (Gomphostilbia) Enderlein, the third largest (206 named species included) in the genus Simulium Latreille s. l., is one of the two most abundant and diverse subgenera in the Oriental Region. To provide a classification scheme to facilitate morphological identification of the species within this subgenus, its diagnostic characters are redefined, and nine known species-groups within it are reviewed. Based on putative lineages explored by using certain adult morphological characters, seven more species-groups are proposed: asakoae, darjeelingense, epistum, gombakense, heldsbachense, hemicyclium and palauense species-groups, while the trirugosum species-group is merged in the varicorne species-group. Subgroups are also introduced to represent apparently different lineages within certain species-groups based on certain pupal morphological characters: two in the banauense species-group, seven in the batoense species-group redefined, four in the ceylonicum species-group redefined, four in the epistum species-group, two in the hemicyclium species-group, two in the sherwoodi species-group and four in the varicorne species-group redefined. A new checklist of species of the subgenus Gomphostilbia, and a key to all 15 species-groups within it are provided. The eastward expansion of the geographical distribution of the subgenus Gomphostilbia is inferred on the basis of the more frequent occurrence of apomorphic characters of certain adult and pupal morphological features in insular species-groups than in continental species-groups. A preliminary attempt using a cladistic analysis of morphological characters shows that among 10 subgenera examined, Gomphostilbia has a sister-taxon relationship with the Australasian subgenus Morops Enderlein, and this clade, together with the Central-Western Pacific subgenus Inseliellum Rubtsov, is positioned closest to the most derived clade formed by Daviesellum Takaoka & Adler and Simulium Latreille s. str.